2003
DOI: 10.1063/1.1531211
|View full text |Cite
|
Sign up to set email alerts
|

Ion beam synthesis of diamond-like carbon thin films containing copper nanocrystals

Abstract: Amorphous carbon thin films containing 0–50 at. % Cu have been grown by mass selected ion beam deposition in order to synthesize isolated Cu nanoparticles within a diamond-like matrix. Raman spectroscopy and x-ray photoelectron spectroscopy show that the sp3 content of the matrix decreases with increasing Cu content. Simultaneously, the mean particle size of the embedded Cu nanocrystals increases, as x-ray diffraction and transmission electron microscopy analysis reveal. There is apparently no dependence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 16 publications
6
36
0
Order By: Relevance
“…The values of band gap of the films deposited with different amount of acetic acid varied between 1.98 and 2.38 eV ( Table 1). The values of E g obtained as above compares well with those obtained for films deposited by plasma CVD techniques [27][28][29][30]. It may be noted here that the energy gap of the clusters depended on the shapes and number of atoms constituting the cluster [16].…”
Section: Optical Studiessupporting
confidence: 59%
“…The values of band gap of the films deposited with different amount of acetic acid varied between 1.98 and 2.38 eV ( Table 1). The values of E g obtained as above compares well with those obtained for films deposited by plasma CVD techniques [27][28][29][30]. It may be noted here that the energy gap of the clusters depended on the shapes and number of atoms constituting the cluster [16].…”
Section: Optical Studiessupporting
confidence: 59%
“…In comparison to previous studies by Gerhards et al [2], the low deposition energy results in a small sputtering coefficient S M . The calculation with SRIM 2006 [9,10] gives a yield for the sputtering of copper on the surface by carbon ions of S CCu = 0.164 and a yield for the sputtering copper on the surface by copper ions of S CuCu = 0.016.…”
Section: Resultsmentioning
confidence: 75%
“…Using immiscible elements, a phase separation with precipitates (clusters) of one element within the other may occur. The deposition parameters (ion energy, provided stoichiometry, temperature) strongly influence the size and distribution of such clusters [2]. A number of studies have shown that this phase separation process can also result in the formation of a self-organized multilayer structure [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Copper doped ta-C films were prepared by our group previously and the film composition as well as the properties of the a-C matrix were investigated using RBS, XPS, TEM and Raman spectroscopy (Gerhards et al 2003).…”
Section: Methodsmentioning
confidence: 99%